MATHEMATICAL LITERACY-BASED LEARNING: WH AT ARE THE CHALLENGES? - Astuti, Furintasari; Mulyatiningsih, Endang; Rosnawati, Raden; Retnawati, Heri (MATEMATIKA DAN PEMBELAJARAN, 2025)
In the educational context, success in the 21st century increasingly depends on students’ mathematical literacy, as it equips them with the ability to reason, solve problems, and make informed decisions based on quantitative information. According to PISA 2018, Indonesian students’ performance in mathematical literacy is significantly below the OECD average, indicating persistent gaps in students’ ability to apply mathematical concepts in real-world contexts. In response, the Indonesian government launched the National Assessment program, which includes the Minimum Competency Assessment consisting of reading literacy and mathematical literacy (numeracy) subtests.  This study aims to analyze how middle school mathematics teachers in Indonesia implement numeracy literacy in their classroom practices, with a focus on identifying the challenges they encounter and the practical solutions they employ. This research adopts a phenomenological approach to explore teachers’ lived experiences in implementing numeracy-based learning. This research is phenomenology research. This study involved 42 mathematics teachers from junior and senior high schools, selected to represent the regions of West Indonesia, Central Indonesia, and East Indonesia. Data was collected using a questionnaire and interviews were conducted through online media. The data were analyzed using Bogdan and Biklen. The results indicate that teachers face several challenges in implementing mathematical literacy–based learning. These include limited socialization and training related to mathematical literacy, insufficient teacher competence, low student interest, restricted instructional time, the need for pedagogical adjustments during the COVID-19 pandemic, and a lack of adequate resources, books, and references on literacy.